The Anglophone Cameroon Predicament - Atanga, Mufor (Book collections on Project MUSE., 2011)
"This study explores the predicament of Anglophone Cameroon - from the experiment in federation from 1961 to the political liberalisation struggles of the 1990s - to challenge claims of a successful post-independence Cameroonian integration process. Focusing on the perceptions and actions of people in the Anglophone region, Atanga argues that what has come to be called the 'Anglophone Problem' constitutes one of the severest threats to the post-colonial nation-state project in Cameroon. As a linguistic and cultural minority, Anglophone Cameroonians realised that the Francophone-led state and government were keener in assimilation than in implementing the federal and bilingual nation agreed upon at reunification in 1960. Calls for national integration became simply a subterfuge for the assimilation of Anglophones by Francophones who dominated the state and government. The book details the various measures undertaken to exploit the Anglophone region's economy and marginalise its people. Principally the economic structures meant to facilitate self-reliant development were undermined and destroyed. Institutionalised discrimination took the form of the exclusion of Anglophones from positions of real authority, and depriving the region of any meaningful development. With the advent of multi-party politics, most Anglophone Cameroonians increasingly have made vocal demands for a return to a federation, in order to adequately guarantee their rights and recognition for them as a political and cultural minority. Actively encouraged by France, the Francophone-led regime in Cameroon has refused to yield to such demands, despite the grave danger of violent conflict and possible secession."--P. [4] of cover.